Prevalence of second-hand tobacco smoke in relation to smoke-free legislation in the European Union - Schiavone, Sara; Anderson, Carrie L.; Mons, Ute; Winkler, Volker (Preventive medicine, 2022)
Exposure to second-hand smoke (SHS) is an important public health problem. We assessed SHS exposure in restaurants and bars across the European Union (EU) and studied associations with country-level smoke-free legislation. Data of Eurobarometer surveys 2014 and 2017 were used to estimate country-specific prevalence of observing smoking in restaurants and bars, which can be considered a marker of SHS exposure. Additionally, we used multilevel logistic regression models to study associations with comprehensiveness of national smoke-free regulations in restaurants and bars, which were derived from the Tobacco Control Scale. In total, 44,809 people from all 28 EU member states were included in the analysis. The results of the multilevel logistic analysis show that in countries with complete and extensive bans, respondents were less likely to have observed people smoking inside restaurants than in countries with partial bans, which represented the lowest level of smoke-free policy implementation (OR 0.24, 95%CI 0.10-0.57 for complete ban and OR 0.23, 95%CI 0.10-0.54 for incomplete but extensive ban). Also, the prevalence of seeing people smoking in a bar was lower in the countries with an extensive ban (OR 0.23 95%CI 0.11-0.45) and with a complete ban (OR 0.20 95%CI 0.10-0.40). Between 2014 and 2017, SHS exposure in restaurants and bars decreased significantly. Our results confirm that in countries with extensive or complete smoking bans, people were less exposed to SHS in restaurants and bars; and that partial bans are less effective in reducing SHS exposure.